New records of the genus Xylaria (Ascomycota, Xylariaceae) from the República Argentina - Hladki, A.I. (2007)
Twelve species of Xylaria are cited as new records from Argentina: Xylaria adscendens, X. allantoidea, X. coccophora, X. cubensis, X. fissilis, X. gracillima, X. luxurians, X. melanura, X. multiplex, X. myosurus, X. kretschmarioidea and X. pseudoapiculata. The last two species are reported for the second time globally. We described for the first time the anamorphic or sterile stromata obtained in culture of X. kretschmarioidea, X. luxurians and X melanura, and cultures in oatmeal-agar of X. pseudoapiculata. X. torulosa is synonymized under X. coccophora, and new substrates and hosts are reported for most species.